MITOS DI BALIK LAPORAN SOSIAL BANK SYARIAH - Ary Yunita Anggraeni; Eko Ganis Sukoharsono; M. Achsin (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2019)
This study aims to understand and interpret the social reports of one of the first Islamic banks in Indonesia contained in the annual report. The analytical tool used in this study is Barthes's semiotics through the stages of interpretation in a denotative and connotative manner. Interpretations made by researchers other than the text also include visual interpretations. In this study it was found that there were inconsistencies in the preparation of social reports, and there were texts and images which aimed to create, build and maintain the positive side of the company in the eyes of the public.